PENEGAKAN HUKUM TINDAK PIDANA PERIKANAN DI PERAIRAN SUMATERA SELATAN: ANALISIS HAMBATAN DAN STRATEGI PENGUATAN PENYIDIKAN DITPOLAIRUD - Imam Shokibi; Erli Salia; Ismail Pettanase (Universitas Labuhanbatu, 2026)
Law enforcement against fisheries crimes constitutes a strategic instrument for safeguarding fisheries sustainability and strengthening state sovereignty over Indonesian waters. South Sumatra Province, characterized by extensive riverine, estuarine, and coastal fisheries, continues to experience a high incidence of illegal fishing, particularly the use of prohibited trawl fishing gear and fishing vessels operating without valid licenses. This study aims to examine the effectiveness of fisheries crime law enforcement conducted by investigators of the Water and Air Police Directorate (Ditpolairud) of the South Sumatra Regional Police and to identify the principal obstacles affecting criminal investigation processes. This research employed an empirical juridical approach using qualitative methods through library research, case document analysis, and interviews with Ditpolairud investigators and relevant stakeholders. The findings reveal that law enforcement remains suboptimal due to three major categories of obstacles. First, internal constraints include limited patrol vessels, an insufficient number of investigators with specialized expertise in fisheries crimes, and inadequate operational funding. Second, external constraints consist of low legal awareness among fishermen, economic pressures encouraging the use of prohibited fishing gear, and the extensive geographical characteristics of South Sumatra's rivers, estuaries, and coastal waters, which complicate surveillance and enforcement activities. Third, structural constraints involve weak inter-agency coordination among Ditpolairud, the Ministry of Marine Affairs and Fisheries, local governments, and the prosecution service, as well as regulatory challenges following amendments to fisheries legislation. These constraints have reduced the effectiveness of criminal investigations, weakened the deterrent effect of law enforcement, and contributed to repeated fisheries violations. The study recommends strengthening the institutional capacity of Ditpolairud through improved operational facilities, specialized investigator training, enhanced inter-agency coordination, and continuous legal awareness programs for fishing communities to improve the effectiveness of fisheries crime law enforcement.Keywords: law enforcement; fisheries crime; Water and Air Police; illegal fishing; criminal investigation